2020
DOI: 10.1038/s41598-020-66614-5
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors and mortality of patients undergoing hip fracture surgery: a one-year follow-up study

Abstract: Hip fracture (HF) remains a main issue in the elderly patient. About 1.6 million patients a year worldwide are victims of a Hf. their incidence is expected to rise with the aging of the world's population. identifying risk factors is mandatory in order to reduce mortality and morbidity. the aim of the study was to identify risk factors of 1-year mortality after HF surgery. We performed an observational, prospective, single-center study at Amiens University Hospital (Amiens, france). After ethical approval, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
32
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 41 publications
5
32
0
2
Order By: Relevance
“…In the present study, the all-cause mortality 1 year after arthroplasty was 23.4%. Previous studies showed that 1-year mortality of hip fracture patients varied between 16.6 to 23.9% according to different study designs [ 14 , 15 ], which were consistent with ours. But we did admit that the 1-year mortality was a little higher in our study.…”
Section: Discussionsupporting
confidence: 91%
“…In the present study, the all-cause mortality 1 year after arthroplasty was 23.4%. Previous studies showed that 1-year mortality of hip fracture patients varied between 16.6 to 23.9% according to different study designs [ 14 , 15 ], which were consistent with ours. But we did admit that the 1-year mortality was a little higher in our study.…”
Section: Discussionsupporting
confidence: 91%
“…The retrospective studies in question enrolled patients with different types of hip fracture (femoral neck vs intertrochanteric fracture), surgery options (total hip arthroplasty, hemiarthroplasty, and internal fixation), and comorbidities between the PNB and non-PNB groups. Since mortality and other functional outcomes of elderly patients with hip fracture were affected by many patient-specific and treatment-related factors, 24 , 25 we believed that selection bias might be a plausible explanation for the conflicting results between previous studies and our own.…”
Section: Discussionmentioning
confidence: 70%
“…Over half had a surgical delay greater than 48 h (181 patients, 58.6%). Factors independently associated with 1-year mortality were: advanced age (HR = 1.06, 95%CI: 1.01–1.12; p =0.032), comorbidities as defined by the revised cardiac index or Lee score ≥ 3 (HR = 1,52, 95%CI: 1,05–2,20; p = 0.026) and surgical delay over 48 h (HR = 1.06, 95%CI = 1.01–1.11; p = 0.024) [ 140 ].…”
Section: Prognostic Factors and Mortalitymentioning
confidence: 99%